Grid based data processing tools and applications for black sea catchment basin - Gorgan, D.; Abbaspour, K.; Cau, P.; Bacu, V.; Mihon, D.; Giuliani, G.; Ray, N.; Lehmann, A. (2011 IEEE 6th International Conference on Intelligent Data Acquisition and Advanced Computing Systems, 2011)
This paper highlights the main functionalities, tools and applications provided by the BSC-OS portal, developed through the enviroGRIDS project. The presentation highlights the main issues of interoperability between geospatial and grid infrastructures, and between different platforms supporting the Earth Science oriented tools and applications. Other subjects such as spatial data management, hydrological model calibration, environmental scenario development and running, satellite image classification and data mining, tools and applications for data reporting and scenarios visualization, and development of Earth Science oriented training materials, are approached by the BSC-OS portal development.